Investigating the effects and mechanisms of HMG-CoA reductase inhibitor simvastatin on the human myometrium - Pang, Vincent (2017)
Preterm birth is responsible for 28% of all early neonatal deaths worldwide (Liu et al., 2015). The primary cause of preterm birth is preterm labour, occurring in 40 – 45% of all preterm deliveries (Goldenberg et al., 2008). Current management alleviates symptoms without disease prevention, due largely to incomplete mechanistic understanding. Emerging evidence suggests a role for cholesterol in the regulation of uterine contractility (Taggart et al., 2000; Kendrick et al., 2004; Smith et al., 2005), with evidence that cholesterol-manipulation agents can affect myometrial contractions. Further research into the effects of cholesterol modulation on myometrial contractility may reveal possible new tocolytics in the treatment of preterm labour.